Serological Antibodies in Inflammatory Bowel Disease: A Systematic Review - Lani Prideaux; Peter De Cruz; Siew C. Ng; Michael A. Kamm (2011)
The diagnosis of inflammatory bowel disease (IBD) is traditionally based on a combination of clinical, endoscopic, histological, and radiological criteria. However, further testing is needed in cases of diagnostic uncertainty and in predicting disease course. This systematic review focuses on the potential for 10 serological antibodies to fill these roles: pANCA, ASCA, anti-OmpC, anti-CBir1, anti-I2, ALCA, ACCA, AMCA, anti-L, and anti-C. We discuss their prevalence in IBD and health; their role in disease diagnosis and risk stratification; their stability over time; their presence in unaffected relatives; their association with genetic variants; and differences across ethnic groups. Serological antibodies have some role in primary diagnosis and in differentiating between Crohn's disease and ulcerative colitis. In indeterminate colitis, preoperative measurement of serological antibodies can help to predict the likelihood of complications among patients undergoing pouch surgery. The combined presence and magnitude of a large panel of antibodies appear to be of value in predicting disease progression. There is currently insufficient evidence to recommend the use of antibody testing to predict responses to treatment or surgery in patients with IBD.